UNI FINDER – A Web-Based System for Assisting in the Selection of University Programme in Malaysia Based on MBTI Personality Types - Mohd Alwi, Irsalina Ilyana Sufi (IRC, 2020)
Personality is an essential part of our lifestyle. This defines how we are living, speaking, responding, showing our desires, and even influencing our mental health. Personality analysis is an innate skill of humans, done by multiple people every day and for countless reasons (Bharadwaj, Sridhar, Choudhary, & Srinath, 2018). Compared to the highly developed country, Malaysia’s education system however is simply focusing on results or what should we say as ‘solely result-oriented’. Thus, this project will be focusing on developing Uni-Finder, a web-based system that will integrate the personality test based on MBTI approach to find a suitable field of study along with a list of universities that offered the suitable courses. This project target users will be mainly focusing on secondary students who are in the phase of late adolescence and early adulthood which are very important period for their career development.